Design and implementation of web-based data dissemination system - Liu, Ying (2014)
As a result of internet expansion and information explosion, volume of information stored in Web contents is largely increased in recent years. Huge expanding of Web content addresses many issues for information management. In this project, a smart data dissemination system with comprehensive content management features is designed to cope with information management problems.